The purpose of this study was to analyze the phisycal and mechanical properties of binderless particleboard using bamboo as raw materials. Andong bamboo (Gigantochloa pseudoarundinaceae) used in this study was taken from Bogor area. Bamboo was converted using hammer mill and air dried subsequently. The particle zise was passed of the 20 mesh screener. Three types pretreatment were used to prepare the particle, namely : 1) water boiling for 30 and 60 minutes, 2) oxydation using hydrogen peroxyde, - SUHASMAN .; Muh. Yusram MASSIJAYA; Yusuf Sudo HADI; Adi SANTOSO (Jurnal Ilmu dan Teknologi Hasil Hutan, 2010)
The purpose of this study was to analyze the phisycal and mechanical properties of binderless particleboard using bamboo as raw materials. Andong bamboo (Gigantochloa pseudoarundinaceae) used in this study was taken from Bogor area. Bamboo was converted using hammer mill and air dried subsequently. The particle zise was passed of the 20 mesh screener. Three types pretreatment were used to prepare the particle, namely : 1) water boiling for 30 and 60 minutes, 2) oxydation using hydrogen peroxyde, and 3) combination of water boiling for 30 minutes and oxydation using hydrogen proxide. As a control, conventional particleboards using 10 % melamine formaldehyde (MF) resin based on dry particle weight was produced. The particle which has pretreated then utilized to produce binderless particleboard with board density of 0.75 g/cm3. The pressing conditions were 180 oC in temperature, 25 kgf/cm2 in pressure for 20 minutes. The board characteristics were tested according to JIS A 5908 2003. The results indicated that particleboard made from  particle with oxydation pretreatment performed superior characteristics compared to those of particleboard made from particle only with water boiling pretreatment. Dimensional stability and modulus of elasticity of board with oxydation pretreatment were excellent. Its was superior compared to that of conventional particleboard using melamine formaldehyde as adhesive.   Keywords : Bamboo, Binderless Particleboard, Oxydation, Hydrogen Peroxyde